Gestational diabetes mellitus as a social problem - Gorczyca, Tomasz; Gorczyca, Daria; Miturski, Andrzej; Balawende, Krzysztof; Mazurek, Diana; Polak, Grzegorz; Maciejewski, Ryszard; Kwaśniewska, Anna (Polish Journal of Public Health, 2013)
The incidence of diagnosing diabetes in pregnancy in different parts of the world is 3-20%. Members of the world-wide organizations dealing with diabetes of the pregnant women emphasize the need of introducing changes in its definition in the foreseeable future. Such changes could significantly increase the rate of diagnosing the disease. Due to the existence of more numerous evidence of decreasing the risk of complications in mother and child as a result of treatment of even mild hyperglycaemia conditions, redefinitions of gestational diabetes mellitus (GDM) are inevitable. Gestational diabetes is diagnosed in a growing number of women in the light of the increasing rates of obesity, type 2 diabetes, as well as the later biological age of women planning to become pregnant. Because of this tendency, and in connection with the proven risk of complications in the mother and child, both during pregnancy and after the birth due to the increased risk of the development of type 2 diabetes in future, the development of diabetes during pregnancy is becoming a growing social problem. The implementation of the appropriate scheme of preventive tests, early diagnosis, and the correct glycemic control may contribute to the limitation of its dangerous effects. Awareness of the value of monitoring over the pregnant woman and the fetus, especially in the presence of the factors of risk of the development of gestational diabetes and the proper perinatological care, are the basic factors used to limit the development of complications. Detection of GDM and the implementation of the appropriate mana-gement are important because the effects of uncontrolled diabetes impinge on the future of both the mother and the child, and thus the next generations.